Determination the Level of Knowledge, Attitude, and Practices Regarding Household Waste Disposal among People in Rural Community of Lahore - Shahzadi, Ambrin; Hussain, Muhammad; Afzal, Muhammad; Gilani, Syed Amir (International Journal of Social Sciences and Management, 2018)
Introduction: Waste disposal is one of the major environmental problems in all over the world. Improper waste disposal causes breeding and may cause infectious diseases like cholera, small pox, and plague, etc. The knowledge of waste disposal is necessary for health of people’s. various study reveal that about 90% of people disposal of waste in open places and use the method of land filling, so increase the problems for health of public and the environment. The study has been carried out for the current status of waste disposal. Methodology: A cross-sectional study was carried out in rural area and 100 household peoples were the population. The Data collected by pre- tested questionnaire and direct interviewing the people about their routine waste disposal. Results: Majority of respondents (72.0%) was aware about adverse effects of improper waste removal and (28.0%) Respondent was not aware.95.0% of people have good attitude about waste disposal. Regarding practices most of respondent (52.0%) had the poor practices towards waste disposal and 41.0% had satisfactory practices. Conclusion: The knowledge regarding waste disposal in the most of respondents was found good and in Minimum of respondents having satisfactory knowledge. In spite of good knowledge, the respondents having poor Practices regarding waste disposal due to lack of awareness, unavailability of public dustbins. Int. J. Soc. Sc. Manage. Vol. 5, Issue-3: 219-224